4z-22=-26+8z

Simple and best practice solution for 4z-22=-26+8z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4z-22=-26+8z equation:


Simplifying
4z + -22 = -26 + 8z

Reorder the terms:
-22 + 4z = -26 + 8z

Solving
-22 + 4z = -26 + 8z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-8z' to each side of the equation.
-22 + 4z + -8z = -26 + 8z + -8z

Combine like terms: 4z + -8z = -4z
-22 + -4z = -26 + 8z + -8z

Combine like terms: 8z + -8z = 0
-22 + -4z = -26 + 0
-22 + -4z = -26

Add '22' to each side of the equation.
-22 + 22 + -4z = -26 + 22

Combine like terms: -22 + 22 = 0
0 + -4z = -26 + 22
-4z = -26 + 22

Combine like terms: -26 + 22 = -4
-4z = -4

Divide each side by '-4'.
z = 1

Simplifying
z = 1

See similar equations:

| -6x-32=2 | | 12=9x+3+6 | | p+1=16 | | 60x+75y=9 | | -8+n=-7 | | (-11)-w=(-36) | | 4x-3-7=-27 | | x-(-15)=10 | | 2y-20=35 | | 4x+7+2x=-5x | | -8(9k+7)=15+3k | | 6x-8x+10=9x+19+13 | | r+8=22 | | 5x+2(x-3)+2x=6x+3(x+2)-4+x | | x+y-24=0 | | 12m=240 | | -12x-2y=-54-3x | | Kx+13-8x=-1 | | -7d-2d=-33 | | -2x+3=.5x+3 | | 2x^2=7x-29 | | 17+a=8 | | 3x-7y=6-5y | | 20n=180 | | 1=X-2x^2 | | 3d=9d-9 | | 29-3c=9(7c+2) | | 6=7y+3 | | 6r-12=3+7r | | -20b=280 | | 345-4532x=12 | | 3y+2-4=6 |

Equations solver categories